Comprehensive Analysis of Risk and Safety Management of Longboat Navigation in Indonesian Waters - Amin, Avi Mukti; Schouten, Femmy; Tampubolon, Freddy; Fauzi, Fauzi; Basri, Erni; Nomin, Nomin (IWJ : Inland Waterways Journal, 2025)
This study evaluates longboat operational safety on the Sampit–Pagatan route in East Kotawaringin, Central Kalimantan. The route is a vital link for remote areas where road infrastructure is lacking. Field data indicate frequent longboat accidents between 2021 and 2024, some fatal, due to limited safety equipment, insufficient crew competence, and substandard vessel seaworthiness. Using a qualitative and quantitative descriptive approach—through field surveys, observations, and regulatory reviews—this study explores the root causes and their implications. Findings highlight a significant correlation between crew knowledge and compliance with safety equipment requirements. This research offers innovation-based safety management recommendations for improved inland navigation standards.